Disruption of the CFTR Gene Produces a Model of Cystic Fibrosis in Newborn Pigs - Rogers, Christopher S. (2008)
Almost two decades after identification of the CFTR gene, we lack answers to many questions about the pathogenesis of cystic fibrosis (CF), and it remains a lethal disease. Mice with a disrupted CFTR gene have greatly facilitated CF studies, but they fail to develop the characteristic pancreatic, lung, intestinal, liver, and other CF manifestations. Therefore, we produced pigs with a targeted disruption of both CFTR alleles. These animals exhibited defective chloride transport. They also developed meconium ileus, exocrine pancreatic destruction, and focal biliary cirrhosis, replicating abnormalities seen in newborn patients with CF. This swine model may provide opportunities to address persistent questions about CF pathogenesis and accelerate discovery of treatments and preventions.